PERTIMBANGAN HAKIM PADA PUTUSAN PRAPERADILAN NO. 97/PID.PRAP/2017/ PN.JKT.SEL DAN N0 04/PID.PRAP/2015/PN.JAK.SEL TENTANG PENETAPAN STATUS TERSANGKA - Dasrinal, Dasrinal (UNES Law Review, 2019)
Determination of suspect status is an extension of the pretrial object. The problem is the consideration of pretrial judges in deciding pretrial applications to determine the status of suspects in case No. 97 / PID.PRAP / 2017 / PN.JKT.SEL and case No. 04 / PID.PRAP / 2015 / PN.JAK.SEL. This research is legal research with analytical descriptive specifications with a normative juridical approach. Normative legal research approach. The results showed that the Judge's consideration of the pretrial request was the validity of the evidence used as the basis for determining the suspect. Another consideration is the object of pretrial requests not the authority of a pretrial judge. Pre-trial Judge's Decision Against Pretrial Request Determination of the Status of Suspects is in part granted the Pre-trial Petitioner in part;